1.5. Enhancing Archaeological Data Collection and Student Learning with a Mobile Relational Database - (:unkn) unknown (My University, 2016)
In 2011, the Proyecto de Investigación Arqueológico Regional Ancash (PIARA) inaugurated an archaeological field school that employed a comprehensive digital data collection protocol. Students learned to record data on iPads using our customized relational databases for excavation, human skeletal analysis, and artifact classification. The databases integrated digital media, such as vector drawings and annotated photos. In a final research project, the students used the tablet system to analyze excavation contexts and artifacts, visualize relationships between the data, conduct literature reviews, and present their findings. This chapter discusses how students develop a greater comprehension of archaeological concepts and stronger research skills when they collect and analyze data using a relational database. More precisely, it argues that the database develops more perceptive archaeologists who can immediately recognize and interpret relationships between archaeological materials, contexts, and features. The technology, then, not only aids in-field planning and interpretation, but also cultivates analytical thinking.
Keywords: digital archaeology; student learning; field school; mobile relational database; rural Peru